First-line therapy of osimertinib with chemotherapy in Chinese patients with EGFR mutation–positive non–small cell lung cancer: protocol for a multicenter, prospective, observational study - Zhang, Bo; Ning, Fangling; Liu, Xiaomei; Li, Na; Wang, Pingfei; Yao, Wenxiu; Han, Baohui; Wang, Qiming; Zhong, Hua (Frontiers in Oncology, 2025)
Epidermal growth factor receptor (EGFR) gene mutations are the most common oncogenic-genomic driver in non-small cell lung cancer (NSCLC), with highest prevalence (30%-50%) in Asian patients. Osimertinib, a third-generation EGFR tyrosine kinase inhibitor (EGFR-TKI) is the preferred first-line (1L) treatment for patients with NSCLC harboring EGFR-TKI- sensitizing mutations (exon 19del and/or exon 21 L858R). The FLAURA2 study suggested that combining chemotherapy with osimertinib treatment significantly improved progression-free survival (PFS) by approximately 9 months compared with osimertinib monotherapy among patients with EGFR-mutated advanced NSCLC. However, there is a lack of real-world efficacy and safety data for osimertinib in combination with chemotherapy, including the selection of different chemotherapy treatment patterns in real-world settings. This multicenter, prospective, observational study will recruit approximately 700 adult Chinese patients with histologically or cytologically documented non-squamous, stage IIIB/IIIC/IV NSCLC, EGFR sensitive mutation (exon 19del or 21 L858R, either alone or in combination with other EGFR mutations) and Eastern Cooperative Oncology Group (ECOG) performance status of 0 to 2 will be eligible to enroll in the study. Eligible patients will receive osimertinib plus chemotherapy as the 1L therapy based on the physician’s medical assessment. The primary endpoint is the median real-world PFS (rwPFS) as assessed by the investigator. Secondary endpoints include treatment pattern and dose intensity of 1L therapy, response rate, duration of response (DoR), overall survival (OS), and safety. Exploratory endpoints include second progression on a subsequent treatment (PFS2), time to treatment discontinuation (TTD), and time to first subsequent treatment (TFST). The central nervous system (CNS) response rate, CNS PFS, subsequent treatment pattern, progression patterns, and the genomic profile in the patients who had disease progression on receiving 1L osimertinib plus chemotherapy. The results of the proposed study aim to contribute evidence on the effectiveness and safety of osimertinib plus chemotherapy with diverse treatment patterns in Chinese patients with advanced NSCLC in real-world settings and support the clinical application of osimertinib-chemotherapy.Trial RegistrationClinicalTrials.gov, identifier NCT06376084 (Date of registration: 17-04-2024).